Incidence of pregnancy in feedlot heifers at slaughter - S.B. Laudert (Kansas Agricultural Experiment Station Research Reports, 1988)
Nearly 83,000 heifers were observed at slaughter during 1986 and 1987 to determine their reproductive status. Slightly less than 4 percent were found to be pregnant. Highest incidences of pregnancy were found during the winter months of November through March. Lowest incidences were found during August, September. and October.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Pregnant feedlot heifers; Reproduction